Calibration of a system for on-line monitoring of electron energy and absorbed dose at an industrial accelerator LU-10 - Pomatsalyuk, R.I.; Tytov, V.Yu.; Titov, D.V.; Uvarov, V.L.; Shevchenko, V.A. (Вопросы атомной науки и техники, 2020)
Particle beam energy and absorbed dose are critical parameters of product processing at industrial electron accelerators. For on-line monitoring of those parameters, a method based on measuring of distribution of the charge induced by irradiation in a wide-aperture stack-monitor, positioned behind an irradiated object, has been developed. A brief review of a control system for monitoring of the processing parameters created with the use of the EPICS package as well as the data of its operating experience at an LU-10 Linac of NSC KIPT are presented in the article. The procedure and results of calibration of the measuring channels within the electron energy range 8…10 MeV are described. Енергія частинок пучка і поглинута доза є критичними параметрами при обробці продукції на промислових прискорювачах електронів. Для on-line моніторингу цих параметрів розроблено метод, що є оснований на вимірюванні розподілу наведеного опромінюванням заряду у широкоапертурному стек-моніторі, який розміщено за оброблюваним об’єктом. Надано стислий огляд системи моніторингу та контролю параметрів обробки, що створена з використанням пакету EPICS, а також дані щодо досвіду її експлуатації на прискорювачі ЛУ-10 ННЦ ХФТІ. Описані процедура та результати калібрування вимірювальних каналів у діапазоні значень енергії електронів 8…10 МеВ. Энергия частиц пучка и поглощенная доза являются критическими параметрами при обработке продукции на промышленных ускорителях электронов. Для on-line мониторинга этих параметров разработан метод, основанный на измерении распределения наведенного облучением заряда в широкоапертурном стекмониторе, который находится за обрабатываемым объектом. Представлены краткий обзор системы мониторинга и контроля параметров обработки, созданной с использованием пакета EPICS, а также данные об опыте ее эксплуатации на ускорителе ЛУ-10 ННЦ ХФТИ. Описаны процедура и результаты калибровки измерительных каналов в диапазоне значений энергии электронов 8…10 МэВ.